The Guatemalan Presence in Latin American Anti-Communist Congresses (1954-1980) - Vázquez Medeles, Juan Carlos (2020)
This work analyzes the different anti-communists meetings of  the Inter-American Confederation for the Defense of the Continent, and the congresses held by the Latin American Anti-Communist Confederation since May 1954. It focuses on Guatemalan participation, its ideological postulates and some of its actions carried out under these contexts. From the hemerographic, archival and documentary review, two moments of structuring of political praxis are noted among the militants of these groups who, in their struggle against communism, passed through the dispute to obtain political power in the 1950s and 1960s to the implementation of counterinsurgency strategies in the 1970s and early 1980s. Likewise, the figure of Mario Sandoval Alarcón (1923-2003) and his process of configuration as the leader of anti-communism stand out, to show the crossovers and transfers of knowledge between the members of these leagues and the mechanisms used in their interconnections.